Pengaruh Puzzle Numerasi terhadap Kemampuan Numerasi Siswa Kelas V di Sekolah Dasar - Anggraini, Dina; Anjarini, Titi; Nurhidayati, Nurhidayati (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to determine the effect of numeracy puzzles on the numeracy skills of 5th grade students at Sidosari Public Elementary School through pretest and posttest results. The research method used is quantitative research with a one-group pretest-posttest pre-experimental design to measure students' numeracy skills. The population used was 22 fifth grade students. The research instrument was AKM (Minimum Competency Assessment) questions in the Teaching Campus program which included pretest and posttest. Data were analyzed using descriptive analysis, normality tests, and statistical tests to determine whether the posttest scores increased significantly compared to the pretest scores. The statistical test used was a non-parametric test because the data was not normally distributed, so it used Wilcoxon Signed Rank. The results showed that the Wilcoxon Signed Rank test showed that there was a difference between the pretest and posttest of students after using numeracy puzzles with Sig. (2-tailed) of 0.000 <0.05. It can be interpreted that H₀ is rejected and H₁ is accepted, so there is an influence of numeracy puzzles on students' numeracy abilities in grade V of Sidosari State Elementary School. In conclusion, there is a significant influence in supporting the use of puzzle-based learning methods as a way to engage students and improve their numeracy abilities, as well as contribute to broader learning in developing critical thinking and problem-solving skills.   Keywords: Numeracy Skills, Media, Numeracy Puzzle.